Double overlapping herald patches in a young child with papular pityriasis rosea – A rare variant of this paraviral exanthem. - Chuh, A.; Fölster-Holst, R.; Zawar, V. (European Journal of Pediatric Dermatology, 2017)
We present a boy aged two-years and five-months with history of atopic dermatitis. He suffered from prodromal coryzal symptoms, followed by the eruption of two ring-shaped overlapping skin lesions at his right lower back five days later. A generalized eruption of secondary lesions was seen another five days later. Most of the secondary lesions were papules. Orientations of the larger lesions were along the lines of skin creases. Peripheral collarette scaling configuration was visible by naked eyes for the larger lesions. Digital epiluminescence dermatoscopy revealed such configuration for the smaller lesions as well. PCR and serological investigations revealed no evidence of primary infection or endogenous reactivation of human herpesvirus-6 or -7. We discussed the possible relevance of double and overlapping herald patches on the etiopathogenesis of pityriasis rosea.